Epidemiology, symptomatology and treatment of patients with myasthenia gravis in an Australian hospital. Issue 12 (5th December 2019) - Li, Vivien; Jasinarachchi, Mahi; Butler, Ernest
Abstract: Myasthenia gravis (MG) is a disorder affecting neuromuscular transmission with heterogeneous manifestations and treatments. This study describes clinical features and management of MG patients at a metropolitan hospital in Australia. Overall findings were consistent with previously published data. However, frequency of intravenous immuno‐globulin use was higher, reasons for which are explored. Management is best conducted through specialist clinics with necessary expertise and standardised treatment protocols.